2012
DOI: 10.1017/s002221511200223x
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided sinus surgery: practical and financial experiences from a UK centre 2001–2009

Abstract: This study provides some evidence that image-guided sinus surgery is cost effective, safe and may decrease surgical revision rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Masterson et al 1216 found a reduction in revision surgery among patients whose ESS was performed with IGS. Other studies have not demonstrated similar benefits of IGS.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…Masterson et al 1216 found a reduction in revision surgery among patients whose ESS was performed with IGS. Other studies have not demonstrated similar benefits of IGS.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
“…One study has proposed that IGS may reduce the overall cost of care, by reducing the need for revision surgery. 1216 From a medicolegal perspective, IGS has not been implicated as a factor in litigation for ESS-related complications 1234 (Table X- …”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
“…Sub-millimeter accuracy in CBCT image overlay on the endoscopic view was achieved. The utility of surgical navigation in endoscopic endonasal skull base surgery is well established [1][2][3][4][5][6][10][11][12][13][14][15]. Most commercially available navigation systems employ a contour-based registration protocol, where a laser pointer is used to identify the skin surface, which is then co-registered with the preoperative CT or MR images [38].…”
Section: Discussionmentioning
confidence: 99%
“…To further increase safety, surgical navigation has been implemented and is today a well-established tool in endoscopic skull base surgery [3][4][5][6]. While some studies have failed to demonstrate a positive impact of navigation in endonasal surgery [7][8][9], others have shown reduced complication rates and improved patient outcome [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, ongoing surgical dissection can alter the observed anatomy on a real time basis and distort boundaries seen on a pre-operative navigational CT scan. It appears that computer guided sinus surgery may not necessarily improve clinical outcome, but it may reduce surgical complication rates [9,10].…”
Section: Introductionmentioning
confidence: 99%